005 OP: ON THE NEED FOR PRACTICE THEORIES IN HEALTH SERVICES AND POLICY RESEARCH: LESSONS FROM QUALITATIVE INQUIRY. Issue 4 (12th April 2015) - Shaw, J
Abstract : Researchers in the fields of health services and policy generally focus on optimizing the organization and practice of health care in order to ensure best possible outcomes for patients and the public. This broad mandate variably entails evaluating the feasibility of new service delivery models, devising interventions that achieve better outcomes, and studying populations to tailor specific health care initiatives and programs. Implied in these various foci of health services and policy research is a normative logic of implementation, which can be formulated something like this: If researchers find the truth, then practitioners should use it. However, the widely discussed and longstanding "gap" between evidence and practice strongly suggests that this "logic" of implementation must not be very logical at all. In this paper I suggest that the lack of "uptake" of research findings in practice provides a gateway to elaborating on two key conceptual issues in health services and policy research. The first issue is regarding what constitutes knowledge in everyday health care practice, otherwise known as epistemologies of practice. The second issue, building on the first, is regarding how the practice of health care providers actually comes to be and thus how it can be changed. Understanding the knowledge and practice of health care providers requires an understanding of practice in its broadest theoretical sense, as the coordinated activities of everyday experience through which our ongoing lives derive their meaning. Drawing on the findings of a comparative qualitative case study of transitions from hospital to home in London, UK and Toronto, Canada, I will illustrate how conceptual advances in theories of practice provide great insight into (a) the knowledge that health care providers create and use in their everyday practice, (b) why health care is practiced exactly the way it is, and (c) how it might be changed for the better. Demonstrating the value of insights from qualitative applications of practice theories, as demonstrated by the qualitative findings presented in this paper, I call for a shift toward the more systematic use of practice theories in health services and policy research.